Does the ethnicity distribution of research participants reflect the eligible population? Survey of participants recruited through a UK mental health Trust - Matthew Hotopf; Kia-Chong Chua; Fiona Gaughran; Juliana Onwumere; Maria Antonietta Nettis; Aikaterini Dima; Amanda Brown; Tanya Shlovogt; Silian Martinez (BMJ Open)
Objectives To compare the ethnicity distribution of research participants recruited through a UK mental health Trust with that of the population receiving clinical care in that Trust and the wider local population.Design Survey of the ethnicity breakdown of participants in eligible studies, compared with Census data for the Trust catchment area and the Trust patient metrics.Setting A London NHS mental health Trust.Participants The survey was sent to principal investigators of studies opened and completed in the Trust between 2012 and 2022, that had recruited 90 or more participants. Data from 22 of 28 eligible studies were collected, yielding a sample of 3279 research participants.Results Results indicated high alignment between research participant ethnicity and Trust patient population across five main ethnicity categories (Asian, Black, Mixed, White, Other). For example, people who identified as ‘any Black ethnic group’ comprised 24.5% of the Census population, 23.8% of the Trust clinical population and 25.4% of the research participant population. The study also identified areas for improvement, including in the recording of ethnicity and in consistency in terms and definitions used.Conclusions Our findings indicate good levels of representation in relation to participant ethnicity in larger-scale research studies recruited through the Trust. Our work highlights the need for ongoing efforts to ensure representativeness in mental health research and for consistent and comprehensive reporting practices.